Techno-Economic Assessment of Associated Gas Fueled Fleets of Reheat Gas Turbine Plants - M.Obhuo; Dodeye Ina Igbong; Silas Oseme Okuma (Journal of Energy Technology and Environment, 2022)
There are various advantages in investing in the commercialization of associated gas for power generation via gas turbines. Some of these advantages include massive energy generation, a high economic return, and a reduction in pollution and environmental deterioration. This paper provides a model and method for optimizing the techno-economics of gas turbine fleets that use associated gas as fuel. The methodology has the potential to be beneficial as a decision-making tool for investors and governments interested in investing in connected gas economic exploitation. The in-house gas turbine performance software (TURBOMATCH) from Cranfield University was used to model a hypothetical but realistic 296MW reheat engine. According to the study, compressor degradation reduced overall optimal power by 3.42%, 2.19%, and 1.09% for three distinct fleets. The research was carried out for one clean fleet and three degraded fleets (optimistic, medium, and pessimistic). The net present value of the clean, optimistic, medium, and pessimistic degraded fleets is 3.03, 2.97, 2.84, and 2.75 billion US dollars, respectively. The effect of the deterioration in the optimistic, medium and pessimistic fleets is 1.86, 6.05%, and 9.02% reductions in the net present values of the project, respectively. The study would be extremely valuable in decision making for associated gas investors and governments.
Keywords: TURBOMATCH; Simulation; Reheat Engine; Optimization; Technoeconomic; Optimized fleets; Energy Generation; Associated gas